Meningitis caused by streptococcus agalactiae in nile tilapia (Oreochromis niloticus): Infection and inflammatory response - Eto, Silas Fernandes; Fernandes, Dayanne Carla; de Moraes, Alessandra Cristina; Alecrim, João Victor da Costa; de Souza, Pedro Galdino; de Carvalho, Fabíola Christian Almeida; Charlie-Silva, Ives; Belo, Marco Antonio de Andrade [UNESP]; Pizauro, João Martins [UNESP] (MDPI, 2020)
Streptococcus agalactiae (Sta) of Lancefield group B is the primary etiological agent of bacterial meningitis in Nile tilapia and newborn humans. Thus, the study of this disease is of fundamental importance for aquaculture and human medicine. Additionally, elucidation of the mechanisms involved in the host–pathogenic response is important for the success of new therapies. In the present study, we elucidated important aspects of the innate immune response in the brain tissue of Nile tilapia (Oreochromis niloticus) infected by Sta. The neuroinflammatory process in the meninges started with the migration of MHC class II and CD68 + cells, production of TNF-alpha, and the effective immune response to Sta was mediated by the increased iNOs+. In conclusion, the present study brings a partial understanding of the pathophysiological and neuroinflammatory mechanisms in meningitis in Sta infected tilapia, enabling important advances in the therapy of this disease as well as the possibility of using this biological model to understand human meningitis.
Keywords: Microglia; Neuropathy; Streptococcosis; Teleost fish